IMPLEMENTATION OF THE INQUIRY-FLIPPED CLASSROOM MODEL ASSISTED BY EDPUZZLE ON STUDENTS' CREATIVE THINKING - Prasetia, Astri; Lukman, Hamidah Suryani; Mulyanti, Yanti (Prima: Jurnal Pendidikan Matematika, 2024)
The purpose of this research is to improve the creative thinking ability of SMP Negeri 1 Cibadak students through the application of Inquiry-Flipped classrom assisted by Edpuzzle. This quantitative research uses a pseudo-experimental method and a control group of pretest and posttest. There were two subjects involved, namely two experimental classes and one control class with a total of 91 students in grade VII of SMP Negeri 1 Cibadak. To analyze the data, a single-track anava test was used with prerequisites, normality and homogeneity tests. A creative thinking ability test instrument was used in this study which showed the findings that the Inquiry-Flipped Classroom model assisted by Edpuzzle was better than the Inquiry-Flipped Classrom model and direct learning.Keywords: Inquiry, Flipped classroom, edpuzzle, creative thinking